2017
DOI: 10.3390/w9110886
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and Lead Sorption/Desorption on Non-Amended and By-Product-Amended Soil Samples and Pyritic Material

Abstract: Batch-type experiments were used to study cadmium (Cd) and lead (Pb) sorption/desorption on forest soil, vineyard soil and pyritic material samples, on the by-products mussel shell, oak ash, pine bark and hemp waste, and on forest soil, vineyard soil and pyritic material amended with 48 t ha −1 of oak ash, mussel shell, and hemp waste. The main results were that the forest soil showed higher Cd and Pb retention than the vineyard soil and the pyritic material. Regarding the byproducts, sorption was in the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…The nitrate nitrogen and ammonium nitrogen contents were 5 mg kg −1 DM NO 3 − -N and 1902 mg kg −1 DM NH 4 + -N. Perna canaliculus shells were used as a substance eliminating the negative effects of o-cresol. The dose of mussel shells was determined based on preliminary studies and literature data [39,40,58,59]. Our previous research [58] showed that Perna canaliculus shells used in the dose of 5 mg kg −1 DM are a very good biostimulator of both biochemical and microbiological activity.…”
Section: Characteristics Of Perna Canaliculus Mussel Mealmentioning
confidence: 99%
“…The nitrate nitrogen and ammonium nitrogen contents were 5 mg kg −1 DM NO 3 − -N and 1902 mg kg −1 DM NH 4 + -N. Perna canaliculus shells were used as a substance eliminating the negative effects of o-cresol. The dose of mussel shells was determined based on preliminary studies and literature data [39,40,58,59]. Our previous research [58] showed that Perna canaliculus shells used in the dose of 5 mg kg −1 DM are a very good biostimulator of both biochemical and microbiological activity.…”
Section: Characteristics Of Perna Canaliculus Mussel Mealmentioning
confidence: 99%
“…Núñez‐Delgado et al . () found that mussel shells are also efficient in cadmium and lead sorption/desorption on forest soil, vineyard soil and pyritic material. Mussel shell has been widely used as a supplement in the poultry industry (Gerry ).…”
Section: The Versatility Of Mussel Wastes and By‐productsmentioning
confidence: 99%